Custom-sized graphene oxide for the hydrolysis of cellulose. (30th April 2021) - Frecha, E.; Torres, D.; Suelves, I.; Pinilla, J.L.
Abstract: Carbon nanostructures have attracted a long-lasting interest in cellulose hydrolysis reaction. Herein, the usefulness of catalyst downsizing is addressed using various graphene oxide (GO) morphologies, including nanofibers (GONF), sheets of few-layers (FLGO) and quantum dots (GOQD). Such materials were obtained from carbon nanofibers by oxidative cutting and subsequent exfoliation and fractioning in size. The synthesis process incorporated numerous active species (S- and O- functional groups) onto the carbon sp 2 -network, whose relative abundance was in some instances tuned by hydrothermal reduction. Chemical and structural analysis of GO materials was performed by XRD, TEM, XPS and elemental analysis. GOQDs, as the smallest particle size GO material, exhibited the highest catalytic activity. However, its behaviour was dependent on the crystalline features of the starting cellulose and the substrate-catalysts interaction degree. Thus, only 17.8% of raw cellulose was depolymerized into sugars after 24 h at 135 °C, which rose to 60.1% upon enhancing its reactivity by ball-milling (8h, 600 rpm). A simple mix-milling of the cellulose with the catalyst for 10 min enabled an effective solid-solid contact, affording complete conversion and 83.5% of glucose. In comparison, 71.3% and 60.4% of glucose was obtained from their sister counterparts: FLGO and GONF, respectively. Graphical abstract: Image 1 Highlights: Quantitative conversion of cellulose into glucose over different graphene oxide morphologies. The influence of oxidation/exfoliation degree of GO on the catalytic activity is discussed. O- and S-functionalities role towards the hydrolysis reaction is disclosed using hydrothermally pre-treated catalysts. Cellulose pre-treatment as an essential stage towards an effective solid cellulose-catalyst interaction.